An analysis of co-movement in equity sector indices - Shari, Aminah (Human Resource Management Academic Research Society, 2021)
This study examines the co-movement among equity sector returns of the Malaysian capital market. The relationship is investigated using Correlation-based on Ordinary Least Square (OLS) and Multivariate-GARCH Dynamic Conditional Correlation (DCC) to examines the volatilities and correlations of sectoral equity indexes. The study uses daily data that ranges from 5 February 1999 to 6 February 2019. The OLS result reveal that there is a strong co-movement between sectoral equity and the stock market prices except in tin and mining sector. While time-varying correlations among sectoral indexes are estimated using MGARCH-DCC, the empirical results from this analysis show that the plantation, properties and tin and mining sectors have negative unconditional correlation with the stock market, which is a good sign of diversification advantages. The findings have important implications helping portfolio managers and investors to understand the co-movement of equity sectors and then formulate policy measures that encourage better portfolio diversification.